COMMUNICATION MODEL IN SOCIALIZING OF URBAN FARMING â€œKAMPUNG BERKEBUNâ€ INNOVATION PROGRAM IN BANDUNG CITY (MODEL KOMUNIKASI DALAM MEMASYARAKATKAN PROGRAM INOVASI URBAN FARMING â€œKAMPUNG BERKEBUNâ€ DI KOTA BANDUNG PROPINSI JAWA BARAT) - R, Henny Sri Mulyani; Suryana, Asep; Sugiana, Dadang (Prodi Teknologi Pendidikan, 2016)
Â An innovation promoted by the government of the city of Bandung in 2014 that urban gardening activities by utilizing their yards, vacant land, alley, dak Â and the other, better known as Urban Farming. This activity was intended for residents of the city of Bandung with the hope of meeting the food needs of the household and supporting urban green open space. The purpose of this study was to determine the model of communication used by the Department of Agriculture and Food Security in the dissemination of innovation Urban Farming